Tb3+-doped LaF3 nanocrystals for correlative cathodoluminescence electron microscopy imaging with nanometric resolution in focused ion beam-sectioned biological samples. Issue 13 (24th January 2017) - Keevend, K.; Stiefel, M.; Neuer, A. L.; Matter, M. T.; Neels, A.; Bertazzo, S.; Herrmann, I. K.
Abstract : Here, we present correlative cathodoluminescence-electron microscopy bioimaging on focused ion beam cut biological samples. Abstract : Here, we report the use of rare earth element-doped nanocrystals as probes for correlative cathodoluminescence electron microscopy (CCLEM) bioimaging. This first experimental demonstration shows potential for the simultaneous acquisition of luminescence and electron microscopy images with nanometric resolution in focused ion beam cut biological samples.